Ity Inclusive Learning Of Culinary Culinary Arts Based On Direct Practice To Develop The Creativity Of Pkbm Hspg Learners - Eva Hudiafa; Ahmad Rizaldi (Universitas Negeri Padang, 2026)
This study aims to describe the implementation of inclusive learning based on direct practice in culinary classes and analyze its contribution to the development of learners' creativity at PKBM HSPG Serang City. The study employed a descriptive qualitative approach involving eleven informants consisting of one academic coordinator, two culinary instructors, one parent/guardian, and seven Package A learners. Data were collected through in-depth interviews, participatory observation, and documentation studies. Data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings indicate that direct practice-based learning enhances learners' creativity, independence, self-confidence, collaboration skills, and willingness to explore new ideas. These improvements were reflected in learners' ability to modify food presentation, make decisions during practical activities, interact with peers, and confidently present their work. The results also reveal that direct practice provides concrete learning experiences that facilitate understanding and support the gradual development of skills according to each learner's abilities. Therefore, inclusive learning based on direct practice can serve as an effective strategy for fostering creativity and vocational skills development among learners in community learning centers.